Analisis makna simbolik upacara tradisi Tedhak Siten - Utami, Rita Widya; Qomariyah, Siti; Sari, Kahrisma; Awaliyah, Srie Moehayatil (Aksara: Jurnal Bahasa dan Sastra, 2023)
Javanese people are people who still maintain rituals that are still related to natural events, or disasters and still carried out in daily life. One of the traditions carried out in Java, namely: Tedhak Sinten, This ceremony is a birth cycle,and  reached the age of seven eight, which is 7x35 days as the ceremony,to  introduce the child for the first time multiplying the land or the earth. This research uses qualitative data research that is used in the form of primary data and secondary data. Preliminary data were obtained from interviews and observations, documentation. In the tedhak sinten procession, secondary data were obtained from books that discussed the tedhak sinten tradition and used the theory of symbolic interaction. The results of this study prove that the Tedhak Sinten procession is diverse, including: babies who ride seven jadah, babies are put in a chicken cage and choose goods, babies are bathed in setaman water and baby's parents spread coins to small children and interactions with the Symbolic Interaction theory that The meaning of tedhak sinten is made through a process of communication and modification in certain meaningful symbols to produce mutual agreement and can be known and accepted by the community.Keywords: Symbolic meaning, Tedhak sinten tradition,meaning of society,Traditions ceremonies